Mapping and Understanding Ethnic Disparities in Length of Schooling: The Case of Ningxia Autonomous Region, China - Björn Anders Gustafsson; Ding Sai (Institute for the Study of Labor (IZA), 2014)
Disparities in length of schooling between the largest Muslim minority in China, the Hui, and the Han majority are investigated. We use household data collected in Ningxia autonomous region in 2007. It is found that compared with Han persons of the same age and gender, Hui persons have shorter educations with the exception of young and middle-aged urban males who have twelve years of schooling, on average. Particularly noteworthy is that as many as 45 percent of adult rural Hui females are not literate. Possible reasons for the shorter educations of Hui in many segments of the population are numerous. We show that the incentive to invest in length of schooling is smaller among Hui than Han as the association between education and income is weaker. We also report that Hui parents spend fewer resources on education than Han parents and that fewer years of schooling for Hui in the first generation helps to explain why Hui persons in the second generation have shorter educations.
Keywords: I24; J15; P35; 330; China; schooling; Hui ethnicity; Han ethnicity; Ningxia; inequality